Aplikasi Bank Sampah Sebagai Alternatif Pengelolaan Sampah Dengan Metode Prototype Berbasis Android - Suprapto; Ramdhan Syaifulloh (Prosiding Sains dan Teknologi, 2024)
The development of information technology has progressed rapidly as humans interact with the internet through mobile devices and computers. These advancements enhance performance and enable various activities to be carried out quickly, accurately, and efficiently, thereby increasing productivity. In Indonesia, rapid technological growth coincides with a rising population, which leads to an increase in waste volume. Waste is the residual material from human activities or natural processes in solid form, generated daily. To address waste management issues, the establishment of waste banks has become an alternative solution. Waste banks serve as collection centers for sorted waste and are also used in social planning to educate the community on environmental health, encourage behavioral changes at the household level the main source of waste and support the implementation of a circular economy. As a result, the community benefits both ecologically and financially. To improve the effectiveness of waste bank management, an Android-based Waste Bank Application using the Prototype Method is proposed. This system provides general information about waste banks and enables customers to monitor deposit and withdrawal transactions in real time through an online savings book. The mobile-based application can be accessed from various smartphones connected to the internet, facilitating waste bank management and encouraging community participation in waste management programs.